2021
DOI: 10.1155/2021/6663591
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Safety of 5-HT1F Receptor Agonist Lasmiditan on Migraine: A Systematic Review and Meta-Analysis

Abstract: Background. Migraine has a great impact on public health. Current acute therapies do not satisfy all migraineurs. The novel serotonin 5-HT1F receptor agonist appears more promising for aborting migraine attacks. Objective. To evaluate the clinical efficacy and safety of lasmiditan in treating acute migraine attacks. Methods. The literature search was performed in PubMed, Embase, and the Cochrane Central Register of Controlled Trials for randomized controlled trials (RCTs) which assessed the effect and safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several meta-analyses have been published based on data from the previously mentioned clinical trials which have demonstrated that lasmiditan is effective at relieving acute migraine pain compared with placebo [47][48][49] with several demonstrating that the 200 mg dose is more effective than the 100 mg dose. [50][51][52] When compared to triptans, lasmiditan has shown lower odds ratios for pain freedom at 2 hours compared with most triptans (OR 1.72, 95% CI 1.06-2.80 to OR 3.40 95% CI 2.12-5.44) as well as pain relief at 2 hours (OR 1.46, 95% CI 1.09-1.96 to OR 3.31, 95% CI 2.41-4.55). Lasmiditan has also been found to have nonsignificant differences in odds ratios compared with small molecule anti-CGRP gepant rescue medications such as ubrogepant and rimegepant for both pain freedom and pain relief.…”
Section: Lasmiditan and Acute Treatment Of Migraine: Place In Therapymentioning
confidence: 99%
“…Several meta-analyses have been published based on data from the previously mentioned clinical trials which have demonstrated that lasmiditan is effective at relieving acute migraine pain compared with placebo [47][48][49] with several demonstrating that the 200 mg dose is more effective than the 100 mg dose. [50][51][52] When compared to triptans, lasmiditan has shown lower odds ratios for pain freedom at 2 hours compared with most triptans (OR 1.72, 95% CI 1.06-2.80 to OR 3.40 95% CI 2.12-5.44) as well as pain relief at 2 hours (OR 1.46, 95% CI 1.09-1.96 to OR 3.31, 95% CI 2.41-4.55). Lasmiditan has also been found to have nonsignificant differences in odds ratios compared with small molecule anti-CGRP gepant rescue medications such as ubrogepant and rimegepant for both pain freedom and pain relief.…”
Section: Lasmiditan and Acute Treatment Of Migraine: Place In Therapymentioning
confidence: 99%